EFFECT OF FUNGICIDES AND PLANT RESISTANCE ACTIVATOR ON COLLETOTRICHUM LEAF SPOT OF SOYBEAN - Y. V. INGLE; C. U. PATIL; K. D. THAKUR; KALYANI INGLE (The Bioscan, 2014)
The efficacy different fungicides and plant resistance activator were evaluated against Colletotrichum Leaf Spot of soybean caused by Colletotrichum dematium f.s.p. truncatum (Andrus and Moore). In field, two sprays of tebuconazole (0.1%) at 25 days interval resulted in minimum disease index (11.76 and 20.49% at 45 and 70 DAS respectively) followed by propiconazole (0.1%), hexaconazole (0.05) and azoxystrobin (0.1%) and it also re- corded highest per cent disease control i.e. 68.91, 66.97, 66.18% and 58.74% respectively over control. Maximum yield (2305 kg/ha) was recorded in tebuconazole sprayed plots followed by propiconazole (2239 kg/ ha), hexaconazole (2181kg/ha), azoxystrobin (2033 kg/ha) and minimum was obtained in untreated control (1160kg/ha). It was also observed that in in vitro study complete inhibition (100%) was achieved by tebuconazole, propiconazole, hexaconazole and azoxystrobin at selected concentrations. Tested plant resistance activator not found efficient as fungicides. Hence, two spray of tebuconazole (0.1%) at 25 days interval has been advocated for management of Colletotrichum Leaf Spot of soybean.